2020
DOI: 10.3390/ijms21114029
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Freezing Procedures Preserve Structural and Functional Properties of Amniotic Membrane for Application in Ophthalmology

Abstract: For decades, the unique regenerative properties of the human amniotic membrane (hAM) have been successfully utilized in ophthalmology. As a directly applied biomaterial, the hAM should be available in a ready to use manner in clinical settings. However, an extended period of time is obligatory for performing quality and safety tests. Hence, the low temperature storage of the hAM is a virtually inevitable step in the chain from donor retrieval to patient application. At the same time, the impact of subzero temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
2
17
1
Order By: Relevance
“…There have been no comprehensive proteomics studies comparing the effects of the various techniques in preserving all the desirable features of AM in human and veterinary medicine. A recent study using identical AM cryopreservation protocol to the present study reported no detrimental effects of dual freezing-thawing cycles on protein concentrations (i.e., EGF, TGF-β1, HGF, bFGF, hyaluronic acid, and laminin), histological and ultrastructure, transparency, and biomechanical properties of the hAM kept in the freezer in a short period of time 34 ; however, AM kept for periods longer than seven days at −80°C presented low concentrations of cytokines. 17 , 28 The findings of this recent study suggest that the short period of the deep-freezing method used herein does not significantly affect the protein composition of AM.…”
Section: Discussionsupporting
confidence: 60%
“…There have been no comprehensive proteomics studies comparing the effects of the various techniques in preserving all the desirable features of AM in human and veterinary medicine. A recent study using identical AM cryopreservation protocol to the present study reported no detrimental effects of dual freezing-thawing cycles on protein concentrations (i.e., EGF, TGF-β1, HGF, bFGF, hyaluronic acid, and laminin), histological and ultrastructure, transparency, and biomechanical properties of the hAM kept in the freezer in a short period of time 34 ; however, AM kept for periods longer than seven days at −80°C presented low concentrations of cytokines. 17 , 28 The findings of this recent study suggest that the short period of the deep-freezing method used herein does not significantly affect the protein composition of AM.…”
Section: Discussionsupporting
confidence: 60%
“…It was interesting to note that the cryopreservation process did not affect some of its biomechanical properties ( Fenelon et al, 2020 ). Similarly, repeated freezing procedures impacted cell viability but not histological and ultrastructure analysis ( Pogozhykh et al, 2020 ).…”
Section: Graft Storage and Effect On Its Propertiesmentioning
confidence: 99%
“…22 In routine clinical practice, various factors play a role in safe storage, such as the storage temperature and its duration. 96 In this regard, the performance of hAM under different cryopreservation times has been researched by Wagner et al performing studies at 0.5, 1, 3, and 6 months after cryopreservation with hAM stored at −80 C with glycerol, such as CPA, and glycerol-free. The results showed higher cell viability of samples cryopreserved in glycerol for up to 3 months of storage.…”
Section: Preservation and Storage Of Native Hammentioning
confidence: 99%